Recycling of crustal material by the Iceland mantle plume: New evidence from nitrogen elemental and isotope systematics of subglacial basalts. (1st March 2016) - Halldórsson, Sæmundur A.; Hilton, David R.; Barry, Peter H.; Füri, Evelyn; Grönvold, Karl
Abstract: We report new nitrogen (N2 ) abundance and isotope (δ 15 N) data for 43 subglacial basaltic glasses from the neovolcanic zones of Iceland, a key locality in studies of mantle plume geochemistry and crust–mantle processes. New helium and argon abundance and isotope data are also reported to supplement previous studies (Füri et al., 2010; Barry et al., 2014 ), allowing elemental ratios (e.g., N2 / 40 Ar ∗ where 40 Ar ∗  = radiogenic 40 Ar) to be calculated. Subglacial basaltic glasses with N2  > 2 μcm 3  STP/g show a wide range in δ 15 N values, from −2.91 to +11.96‰ (vs. Air), with values >6‰ only observed at one locality in the Eastern Rift Zone. Elemental ratios involving N2, i.e., N2 / 3 He, and N2 / 40 Ar ∗, span several orders of magnitude from 2.5 × 10 5 to 9.0 × 10 7, and 32.8 to 1.46 × 10 6, respectively. In contrast, argon isotope ratios ( 40 Ar/ 36 Ar) are limited, ranging from air-like (∼298.6) values up to 1330. Glasses exhibit a wide range in helium isotope ratios (8–26 R A ), with clear distinctions between individual rift segments. A number of processes have extensively modified original mantle source N isotope and relative abundance compositions – most significantly air interaction, crustal contamination in some instances, and possibly degassing-induced fractionation. Under the assumption that the starting 4 He/ 40 Ar ∗ production ratio of Iceland mantle is identical to the depleted MORB mantle (DMM), a filtering protocol for the entire N dataset, based upon 40 Ar/ 36 Ar and 4 He/ 40 Ar ∗ ratios, was adopted to identify samples with unmodified δ 15 N values. Consequently, we identify 22 samples that define the Icelandic mantle N-isotope distribution (δ 15 N = −2.29 to +5.71‰). Using the filtered dataset, we investigate simple binary mixing scenarios involving N2 / 3 He–N2 / 40 Ar ∗ –δ 15 N variations to identify mantle end-member compositions. Mixing scenarios are consistent with a recycled component in the Iceland mantle source, defined by a high and heterogeneous δ 15 N end-member. Moreover, this end-member is coupled to the high 3 He/ 4 He signature, and is characterized by He depletion and/or the presence of excess N2 . These features strongly suggest the presence of recycled crustal N-component(s) integrated into and/or entrained by the Iceland plume source. These new results reveal the highly heterogeneous nature of nitrogen in the hybrid Iceland plume source, consistent with models based on trace elements and radiogenic isotopes that advocate for significant heterogeneity of recycled crustal component(s) sampled by the Iceland plume. A relatively young age of the recycled crustal material (possibly Phanerozoic) is consistent with the association of positive δ 15 N values and high N2 / 40 Ar ∗ ratios with constraints from radiogenic isotopes (e.g., Pb), thus indicating a relatively short time-interval (∼10 8  years) between subduction of crustal material and entrainment by the Iceland mantle plume.